Mandarin Language Learning from a Sociocultural - Azizah, Mir'ah (Wen Chuang:Journal of Foreign Language Studies, Linguistics, Education, Literatures, Cultures, and Sinology, 2025)
Language is inseparable from sociocultural influences because the use of language is a reality of communication that occurs within social interactions. This article uses the systematic literature review method, which involves an in-depth study and references from articles, books, and research journals. The purpose of this study is to explore Mandarin language learning from a sociocultural perspective. Language and culture, when viewed in balance, are considered significant in foreign language teaching. The success of communication between two communicators from different cultural backgrounds does not rely solely on mastery of linguistic aspects, including grammar and sociopragmatic structures, but also on the ability to perceive, understand, and empathize with the culture of the communication partner. This highlights the harmony that should exist between foreign language and culture learning and one’s own language and culture.Keyword: Learning, Mandarin language, Sociocultural aspects.